Interactive effects between nest microclimate and nest vegetation structure confirm microclimate thresholds for Lesser Prairie-Chicken nest survival - Grisham, B. A.; Godar, A. J.; Boal, C. W.; Haukos, David A. (My University, 2017)
The range of Lesser Prairie-Chickens (Tympanuchus pallidicinctus) spans 4 unique ecoregions along 2 distinct environmental gradients. The Sand Shinnery Oak Prairie ecoregion of the Southern High Plains of New Mexico and Texas is environmentally isolated, warmer, and more arid than the Short-Grass, Sand Sagebrush, and Mixed-Grass Prairie ecoregions in Colorado, Kansas, Oklahoma, and the northeast panhandle of Texas. Weather is known to influence Lesser Prairie-Chicken nest survival in the Sand Shinnery Oak Prairie ecoregion; regional variation may also influence nest microclimate and, ultimately, survival during incubation. To address this question, we placed data loggers adjacent to nests during incubation to quantify temperature and humidity distribution functions in 3 ecoregions. We developed a suite of a priori nest survival models that incorporated derived microclimate parameters and visual obstruction as covariates in Program MARK. We monitored 49 nests in Mixed-Grass, 22 nests in Sand Shinnery Oak, and 30 nests in Short-Grass ecoregions from 2010 to 2014. Our findings indicated that (1) the Sand Shinnery Oak Prairie ecoregion was hotter and drier during incubation than the Mixed- and Short-Grass ecoregions; (2) nest microclimate varied among years within ecoregions; (3) visual obstruction was positively associated with nest survival; but (4) daily nest survival probability decreased by 10% every half-hour when temperature was greater than 34°C and vapor pressure deficit was less than - 23 mmHg during the day (about 0600-2100 hours). Our major finding confirmed microclimate thresholds for nest survival under natural conditions across the species' distribution, although Lesser Prairie-Chickens are more likely to experience microclimate conditions that result in nest failures in the Sand Shinnery Oak Prairie ecoregion. The species would benefit from identification of thermal landscapes and management actions that promote cooler, more humid nest microclimates. © 2016 Cooper Ornithological Society.
Citation: Grisham, B. A., Godar, A. J., Boal, C. W., & Haukos, D. A. (2016). Interactive effects between nest microclimate and nest vegetation structure confirm microclimate thresholds for Lesser Prairie-Chicken nest survival. Condor, 118(4), 728-746. doi:10.1650/CONDOR-16-38.1
Keywords: Empirical Distribution Functions; Humidity; Kansas; Lesser Prairie-Chicken; Microclimate; Nest Survival